2001
DOI: 10.1016/s0167-4889(01)00106-9
|View full text |Cite
|
Sign up to set email alerts
|

A novel and highly divergent Arabidopsis cyclin isolated by complementation in budding yeast

Abstract: A novel cyclin, CycJ18, was isolated by complementation of G1 cyclin-deficient budding yeast with an Arabidopsis cDNA library. CycJ18 shares only 20% identity in its conserved cyclin box domain with other cyclins, and is predominantly expressed in young seedlings. CycJ18 is a member of a potential new plant cyclin class.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Several groups reported that aggregation prone proteins can sequester other non-aggregating proteins, provided that they are structurally similar to each other (Garcia-Mata et al, 2002;Suhr et al, 2001). Since D2SV harbors the majority of wellconserved cyclin box sequence (Abrahams et al, 2001), we reasoned that the intracellular aggregates formed by this protein might sequester other cell cycle proteins containing a cyclin box or cyclin box interacting domains by a process previously described as analogue co-aggregation (Garcia-Mata et al, 2002). In cells overexpressing D2SV, we found that this protein coaggregates with endogenous or transfected cell cycle proteins such as cycD1, cycD2, cycB1 and CDK4.…”
Section: D2sv and Cell Cycle Regulationmentioning
confidence: 99%
“…Several groups reported that aggregation prone proteins can sequester other non-aggregating proteins, provided that they are structurally similar to each other (Garcia-Mata et al, 2002;Suhr et al, 2001). Since D2SV harbors the majority of wellconserved cyclin box sequence (Abrahams et al, 2001), we reasoned that the intracellular aggregates formed by this protein might sequester other cell cycle proteins containing a cyclin box or cyclin box interacting domains by a process previously described as analogue co-aggregation (Garcia-Mata et al, 2002). In cells overexpressing D2SV, we found that this protein coaggregates with endogenous or transfected cell cycle proteins such as cycD1, cycD2, cycB1 and CDK4.…”
Section: D2sv and Cell Cycle Regulationmentioning
confidence: 99%
“…Also, the human K/L/T-and Arabidopsis T-types of cyclins are distantly related to the C-and H-type cyclins, whereas the U-type cyclins might be even more distantly related. In addition to these and the D-type cyclins, there are two more cyclins, SDS and CycJ18 (Abrahams et al, 2001;Azumi et al, 2002), which are quite isolated from others and thus need to be treated as two separate classes. In this paper, we call them SDSand CycJ18-type cyclins, respectively (Fig.…”
Section: The Arabidopsis Cyclins Can Be Grouped Into 10 Typesmentioning
confidence: 99%
“…Poorly characterized groups of cyclins include L, T, C, and H families from plants and animals, and some divergent groups of plant cyclins designated SOLO DANCERS (Azumi et al, 2002), J (Abrahams et al, 2001), and either U (Wang et al, 2004) or P (Torres Acosta et al, 2004). Some of the U/P family members can bind CDKA in a yeast two-hybrid assay (Torres Acosta et al, 2004), but there is no direct evidence for their cell cycle involvement.…”
Section: Cyclin Familymentioning
confidence: 99%